Pengaruh Lama Fermentasi Terhadap Kualitas Jerami Padi Amoniasi yang Ditambah Probiotik Bacillus Sp - Sofyan Damrah Hasan; Oscar Yanuarianto; muhammad Iqbal; muhammad amin (Faculty of Animal Husbandry, University of Mataram, 2015)
The effect of fermentation duration at improving the quality of ammoniation rice straw with Bacillus sp.probiotic was conducted from July to August 2012. This work was arranged in Completely Randomized Design with four treatments and two replications. The treatments were fermented with 3% Bacillus sp for 0, 10, 20, and 30 days imposed to rice straw with ammoniation.Variables observed were crude protein, crude fiber, NDF, ADF, cellulose, hemicellulose and in vitro digestibility. The result of this study showed that duration of fermentation influenced significantly (P<0,05) on chemical composition and in vitro digestibility. In conclusion, the duration of fermentation influenced on chemical composition and in vitro digestibility. The longer the fermentation duration the higher the content of crude protein and in vitro digestibility. Meanwhile, the proportion of crude fiber, NDF, ADF, cellulose, hemicellulose and lignin decreased respectively.